In the shadow of performance and repression: the micromanaged child - Welman, Alissa (The Stellenbosch Socratic Journal, 2024)
This paper explores the phenomenon of overparenting by analysing behaviours associated with overparenting, such as obsessing over a child’s achievements or weight, using Marcuse’s notions of surplus repression and the performance principle. The literature on the micromanagement of children reveals a pattern, and motivations of overparenting, that can be understood in light of the Freudian concepts of repression and identity. By taking a closer look at the micromanagement of childhoods, parents can be interpreted as producers of surplus repression that concentrate the pressures of capitalism on their child. This paper proposes the term ‘surplus-parenting’ as a micro manifestation of surplus repression on a societal level as discussed by Marcuse. By using the term surplus-parenting, the author is able to articulate the consequences of surplus repression in the lives of the children and parents on this micro and macro scale. By questioning the motivations of overparenting, the concepts of the performance principle and surplus repression can be seen as manifesting in the parent-child identity.